PERAN ORGANISASI MAHASISWA DALAM MEMBANGUN KARAKTER KEPEMIMPINAN DAN PENINGKATAN SOFT SKILL - Shinta Yolanda; Suci Maela Sari; Iriani Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The study aims to examine the role of student organizations in building leadership character and improving soft skills. By using a qualitative approach method. The main source was obtained from in-depth interviews with students at Trunojoyo University, Madura, where 10 respondents were selected based on certain criteria that were relevant to the research objectives. The research results show that student organizations have a significant positive impact on developing leadership character and improving soft skills among students. Through active involvement in organizations, students can hone a variety of skills, including communication, collaboration, time management, and problem solving.